Molecular characterisation of Haemoglobin Constant Spring and Haemoglobin Quong Sze with a combine-amplification refractory mutation system - Wee, Yong Chui; Tan, Kim Lian; Chua, Kek Heng; George, Elizabeth; Tan, Mary Anne Jin Ai (Penerbit Universiti Sains Malaysia, 2009)
Background: The interaction of the non-deletional α +- thalassaemia mutations Haemoglobin Constant Spring and Haemoglobin Quong Sze with the Southeast Asian double α-globin gene deletion results in non-deletional Haemoglobin H disease. Accurate detection of non-deletional Haemoglobin H disease, which is associated with severe phenotypes, is necessary as these mutations have been confirmed in the Malaysian population.